2022
DOI: 10.3389/falgy.2022.1029184
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic and pathologic characterization of a novel swine biomedical research model for eosinophilic esophagitis

Abstract: Eosinophilic esophagitis (EoE) is a chronic allergy-mediated condition with an increasing incidence in both children and adults. Despite EoE's strong impact on human health and welfare, there is a large unmet need for treatments with only one recently FDA-approved medication for EoE. The goal of this study was to establish swine as a relevant large animal model for translational biomedical research in EoE with the potential to facilitate development of therapeutics. We recently showed that after intraperitonea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…Cortes et al. showed that after intraperitoneal sensitization and oral challenge with a food allergen, swine develop esophageal eosinophilia, which closely mimics human EoE 11 . This model not only induces the underlying immune markers but also the micro‐ and macro‐pathological hallmarks of human EoE.…”
Section: Selection Of Laboratory Animals and Their Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortes et al. showed that after intraperitoneal sensitization and oral challenge with a food allergen, swine develop esophageal eosinophilia, which closely mimics human EoE 11 . This model not only induces the underlying immune markers but also the micro‐ and macro‐pathological hallmarks of human EoE.…”
Section: Selection Of Laboratory Animals and Their Characteristicsmentioning
confidence: 99%
“…Cortes et al showed that after intraperitoneal sensitization and oral challenge with a food allergen, swine develop esophageal eosinophilia, which closely mimics human EoE. 11 This model not only induces the underlying immune markers but also the micro-and macro-pathological hallmarks of human EoE. However, pigs are expensive, have a long breeding cycle, and are more complex to operate than rodents, which limits their large-scale use in medical research.…”
Section: S Elec Tion Of L Abor Atory Animal S and Their Char Ac Teris...mentioning
confidence: 99%